Efficacy and Safety of Dapsone Versus Trimethoprim/Sulfamethoxazol for Pneumocystis Jiroveci Prophylaxis in Children With Acute Lymphoblastic Leukemia With a Background of Ethnic Neutropenia. Issue 3 (April 2017) - Nazir, Hanan F.; Elshinawy, Mohamed; AlRawas, Abdulhakim; Khater, Doaa; Zadjaly, Sherin; Wali, Yasser
Abstract : Study Objective: To study dapsone in comparison with trimethoprim/sulfamethoxazole (TMP/SMX) for Pneumocystis jiroveci (PJP) prophylaxis in children with acute lymphoblastic leukemia (ALL). Design: A retrospective study with a prospective follow-up. Patients: Pediatric ALL patients diagnosed between May 2009 and May 2014, who are still receiving or have completed their maintenance chemotherapy. Patients who completed chemotherapy were prospectively followed up for neutropenia. Methods: TMP/SMX was used as the initial PJP prophylaxis. An alternative drug was indicated if the patient remained cytopenic for >3 weeks. Average absolute neutrophilic count (ANC), average % of oral mercaptopurine (6-MP), and methotrexate doses were calculated over a period of 6 months before and after shifting to dapsone. Results: Sixty-two ALL patients were eligible for analysis. Twenty-four patients (38.7%) received TMP/SMX for PJP prophylaxis, whereas 34 patients received Dapsone (54.8%). Only 3 patients received IV pentamidine (4.8%), whereas 1 patient (1.6%) received atovaquone. The incidence of prophylaxis failure was 1/1041 months on TMP/SMX and 1/528 months on dapsone. After shifting to dapsone, patients maintained significantly higher ANC (1.46±0.46 vs. 1.17±0.40, P =0.0053), and received significantly higher doses of 6-MP (62.61%±11.45 vs. 57.45±10.14, P =0.0081) and methotrexate (64.9%±14.29 vs. 56.5%±9.9, P =0.0176), with a significantly shorter duration of chemotherapy interruption (1.94±1.2 vs. 3.25±1.29 wk, P =0.0002). Conclusions: Dapsone for PJP prophylaxis in ALL allowed patients to maintain higher ANC and to receive higher doses of chemotherapy, while maintaining a low incidence of PJP breakthrough infection.